Determinants of vaccine acceptance, knowledge, attitude, and prevention practices against COVID‐19 among governmental healthcare workers in Addis Ababa and Adama, Ethiopia: A cross‐sectional study - Aderajew M. Girmay; Mesaye G. Weldegebriel; Melaku G. Serte; Daniel A. Dinssa; Tsigereda A. Alemayehu; Moa A. Kenea; Abel Weldetinsae; Kirubel T. Teklu; Sisay D. Mengesha; Zinabu A. Alemu; Belaynesh Demisie; Bedasa Wagari; et al. (Health Science Reports, 2023)
Abstract Background and Aims COVID‐19 vaccines are vital tools for infection prevention and control of the pandemic. However, coronavirus immunization requires acceptance among healthcare workforces and by the community. In Ethiopia, studies focused on determinants of vaccine acceptance, knowledge, attitude, and prevention practices (KAP) contrary to the novel coronavirus among healthcare staff are limited. Hence, closing this gap requires research. Methods A cross‐sectional study was conducted on 844 governmental healthcare workers. A stratified, simple random sampling technique was used to select the respondents. Data were collected using a structured questionnaire. Binary and multivariable logistic regression statistical models were used to analyze the data. Results This study indicated that only 57.9% of the participants had good COVID‐19 vaccine acceptance, meaning they took at least a dose of the vaccine themselves. We found that 65%, 60.9%, and 51.3% of the participants had good knowledge, prevention practices, and attitude against the pandemic. The novel coronavirus vaccine acceptance rate was 2.19 times more likely among females (adjusted odds ratio [AOR] = 2.19 with 95% confidence interval [CI]: 1.54–3.10) than among male participants. Further, respondents who did not report having any chronic diseases were 9.40 times higher to accept COVID‐19 vaccines (AOR = 9.40 with 95% CI: 4.77, 18.53) than those who reported having a chronic condition. However, healthcare workers who had a habit of chewing khat at least once per week were 4% less likely to take the vaccine (AOR = 0.04 with 95% CI: 0.01, 0.32) than those who had no habit of chewing khat. Conclusion Many core factors influencing COVID‐19 vaccine acceptance were identified. A significant number of participants had poor vaccine acceptance, KAP against COVID‐19. Therefore, the government should adopt urgent and effective public health measures, including public campaigns to enhance public trust in COVID‐19 vaccines. In addition, continuous, timely, and practical training should be provided to healthcare workers.